2023
DOI: 10.3390/su15032104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renewable Energy Sources on the Sustainable Development of the Economy and Greenhouse Gas Emissions

Abstract: Growing population and limited energy resources have impacted energy consumption. Limited fossil fuel resources and increased pollution threaten national and human societies. These elements emphasize energy sources. Renewable energy use affects growth. All new energy sources, including renewables, are crucial for global economic growth. Economic and environmental issues have led to new approaches in international environmental law, including the green economy. This study employs structural vector auto-regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Since thermal energy production reached its improvement limits, those ratios are the same worldwide. The fundamental difference between traditional energy sources (e.g., coal, gas, oil) and renewable ones (e.g., sun, wind) is the limited direct impact of renewable-based energy power plants on the environment [57,58]. The thermal energy environmental losses structure is as follows: direct damages are 80% and the indirect specific damages per unit of output are 20% [59].…”
Section: Resultsmentioning
confidence: 99%
“…Since thermal energy production reached its improvement limits, those ratios are the same worldwide. The fundamental difference between traditional energy sources (e.g., coal, gas, oil) and renewable ones (e.g., sun, wind) is the limited direct impact of renewable-based energy power plants on the environment [57,58]. The thermal energy environmental losses structure is as follows: direct damages are 80% and the indirect specific damages per unit of output are 20% [59].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Muazu et al (2023) found that the dominance of non-renewable resources in certain regions, such as Africa, hinders the transition to renewable energy and negatively affects economic growth. However, Arian et al (2020), Zhang et al (2021), Aydin (2022), Chen et al (2022) and Candra et al (2023) found that the use of renewable energy has a positive impact on economic growth in both middle-and high-income countries in the short and long-term, suggesting that renewable energy contributes directly to economic growth. Other studies, such as Akram et al (2021) and Asiedu et al (2021), showed a bidirectional causal association between renewable energy and economic progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature recommends; the usage of sustainable urbanization, research in the agriculture sector, usage of clean/renewable energy, efficient utilization of resources (circular economy), and the export of inherent GHGs emissions so the usage of clean technologies 43 to replace the production process (technical effect) and other adaptation measures. Reference 44 discussed the factors including energy resources which are influencing economic growth. Environment and economic growth nexus is leading to new international agreements for green economies.…”
Section: Literature Reviewmentioning
confidence: 99%